Deciphering antidiarrheal effects of Meda pata (Litsea glutinosa (Lour.) C.B.Rob.) leaf extract in chemical-induced models of albino rats. (23rd May 2023) - Anjum, Nazifa; Hossain, Md. Saddam; Rahman, Md. Atiar; Rafi, Md. Khalid Juhani; Al Noman, Abdullah; Afroze, Mirola; Saha, Srabonti; Alelwani, Walla; Tangpong, Jitbanjong
Abstract: Ethnopharmacological relevance: Diarrhea is one of the leading causes of preventable death in developing countries, mainly caused by bacterial infections and traditional therapies are very common in diarrheal incidences. Meda Pata ( Litsea glutionsa ) has a long history of use as traditional medicine for diarrhea, dysentery, and spasm in Bangladesh, India, and some other Asian countries. Aim of the study: This research reports the antidiarrheal effects of Meda Pata ( Litsea glutinosa leaf extract, LGLEx) in animal models. The work has been supported by in silico molecular docking study to verify the effects. Materials and methods: The antidiarrheal effect of LGLEx was investigated in castor oil-induced diarrhea, magnesium sulfate-induced diarrhea, and gastrointestinal motility test models. Antidiarrheal effects were supported by a molecular docking study through an interaction between LGLEx's GC-MS analyzed imidazole-containing compounds and muscarinic acetylcholine receptor (PDB: 4U14 ) and 5-HT3 receptor (PDB: 5AIN ). Results: LGLEx potentially reduced the diarrheal incidences in in vivo assays reducing gastrointestinal motility. The maximum diarrheal inhibition was obtained in the castor oil-induced model (62.63%) and and BaSO4 -induced model (73.14%), which were statistically significant (P < 0.05) when compared to the reference drug loperamide. In the castor-oil and BaSO4-induced models, peristaltic movement was reduced by 25.96% and 32.17%, respectively. Biochemical markers particularly IgE, C-reactive proteins, and serum electrolytes were significantly (P < 0.0) restored in treated groups. A Molecular docking analysis revealed that two compounds (1-Ethyl-2-hydroxymethylimidazole and 1, 6-Anhydro-beta-D-glucofuranose demonstrated the highest binding affinity with target receptors muscarinic acetylcholine receptor (PDB: 4U14 ) and 5-HT3 receptor (PDB: 5AIN ) confirming their drug likeliness. The findings indicate a high potential antidiarrheal impact that warrants further investigation for its therapeutic application. Graphical abstract: Image 1 Highlights: Leaf extract of Meda Pata ( Litsea glutinosa, LGLEx) was tested against diarrhea-causing bacteria. Diarrheal inhibition was promising by medium dose in Castor oil-and magnesium sulfate-induced diarrhea. Peristalsis index was reduced in gastrointestinal motility tests. C-reacTive protein, IgE, Creatinine and lipid profiles were improved. Serum electrolytes of animals were about to be restored.